Neuronal guidance: a redox signal involving Mical. - Bernstein, B.W.; Bamburg, J.R. (Current Biology, 2010)
Mical, a redox enzyme, binds the cytoplasmic domain of the semaphorin receptor plexin A and mediates semaphorin-signaled collapse of the actin cytoskeleton. Recent work now shows that Mical's ability to bind actin filaments and destabilize them in a NADPH-dependent manner is responsible for semaphorin 1a's effects.